If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + 2b = p Solving 2a + 2b = p Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2b' to each side of the equation. 2a + 2b + -2b = -2b + p Combine like terms: 2b + -2b = 0 2a + 0 = -2b + p 2a = -2b + p Divide each side by '2'. a = -1b + 0.5p Simplifying a = -1b + 0.5p
| 4n+9-6-3= | | X^3-6x^2=9x-54 | | 5x+7=7+x | | 12x-16=7x-3 | | 6y+4=6y-30 | | 0.23x=4.9+.3x | | (9x-5)(4x-5)= | | -3(-2x+2)=2x-18 | | 30x+(x^2+40x)+10x+35=180 | | 2p+3n=m | | x-(6/13)=4/13 | | X+4=3x-18 | | -3(2x-9)+2x=43 | | 7.50t=187.50 | | 18x+11=2(6x+2)+6x+7 | | 4.2+2.1x=6.3 | | 18÷2/3 | | 3n+2p=m | | 400/-9 | | 2x^2-9=3 | | 15/96 | | 12n^2+4n= | | 2x+10+4=-8 | | M^3y-27y= | | 8(4-2n)=-16n+16 | | 5(1+c)=6(2-c) | | 66/0.03= | | x=4.32 | | 4.05*0.2= | | 4(x-5)2x-1+3= | | -2(c+4)=-50 | | 4x+2=-2x-16 |